2022
DOI: 10.1126/sciadv.abj1325
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of the deep-Earth carbon cycle in response to the Cambrian Explosion

Abstract: Earth’s carbon cycle is strongly influenced by subduction of sedimentary material into the mantle. The composition of the sedimentary subduction flux has changed considerably over Earth’s history, but the impact of these changes on the mantle carbon cycle is unclear. Here, we show that the carbon isotopes of kimberlite magmas record a fundamental change in their deep-mantle source compositions during the Phanerozoic Eon. The 13 C/ 12 C of kimberlites before ~250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…In addition, apart from carbonate minerals, water and aluminosilicates may also serve as sources of oxygen for the generation of deep CO 2 13 , 23 , 68 . Furthermore, in conjunction with the frequently documented process of transferring carbon from organic sources to carbonate minerals 4 , the hydrogen originating from organic compounds, in combination with water-derived hydrogen, could become integrated into hydrous minerals at elevated temperatures, implying a potential impact of surface-level biogeochemical processes on the deeper geosphere 69 , 70 . We are not intent to dismiss the catalytic models that may significantly accelerate organic–inorganic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, apart from carbonate minerals, water and aluminosilicates may also serve as sources of oxygen for the generation of deep CO 2 13 , 23 , 68 . Furthermore, in conjunction with the frequently documented process of transferring carbon from organic sources to carbonate minerals 4 , the hydrogen originating from organic compounds, in combination with water-derived hydrogen, could become integrated into hydrous minerals at elevated temperatures, implying a potential impact of surface-level biogeochemical processes on the deeper geosphere 69 , 70 . We are not intent to dismiss the catalytic models that may significantly accelerate organic–inorganic interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Although the isotopic composition of CO 2 emitted at ocean islands remains poorly constrained, there are suggestions that CO 2 in samples from the Pitcairn hotspot may be isotopically light compared to mid-ocean ridges ( 38 ). Additionally, a recent study on kimberlites, which may be derived from mantle plumes similar to ocean island basalts, showed that δ 13 C in many Phanerozoic examples exhibit low values, which the authors attribute to subducted organic C ( 39 ). The model assumes that organic C is released on the order of hundreds of millions of years after subduction, corresponding to the timescale of convective overturn in the mantle ( 24 , 40 ).…”
Section: Introductionmentioning
confidence: 99%
“…These xenocrysts and xenoliths can provide key information regarding the composition and history of the lithosphere at the time of magma emplacement (e.g., Dalton et al., 2020; Gardiner et al., 2020; Giuliani & Pearson, 2019; Xiang et al., 2022). Furthermore, the temporal distribution of kimberlites throughout Earth's history, which encompasses a period of more than 2.5 Gyr (Heaman et al., 2019; Woodhead et al., 2019), may record secular cooling of the mantle, geodynamic processes (i.e., the onset and evolution of plate tectonics), and supercontinent cycles (e.g., Giuliani et al., 2022; Stern et al., 2016; Tappe et al., 2018). As such, it is essential to obtain reliable kimberlite ages.…”
Section: Introductionmentioning
confidence: 99%
“…, may record secular cooling of the mantle, geodynamic processes (i.e., the onset and evolution of plate tectonics), and supercontinent cycles (e.g., Giuliani et al, 2022;Stern et al, 2016;Tappe et al, 2018). As such, it is essential to obtain reliable kimberlite ages.…”
mentioning
confidence: 99%